Proteotranscriptomic analyses reveal distinct interferon-beta signaling pathways and therapeutic targets in choroidal neovascularization - Hu, Yuxiang; Qi, Siyi; Zhuang, Hong; Zhuo, Qiao; Liang, Yu; Kong, Hongyu; Zhao, Chen; Zhang, Shujie (Frontiers in Immunology, 2023)
Aim To investigate the molecular mechanism underlying the onset of choroidal neovascularization (CNV). Methods Integrated transcriptomic and proteomic analyses of retinas in mice with laser-induced CNV were performed using RNA sequencing and tandem mass tag. In addition, the laser-treated mice received systemic interferon-β (IFN-β) therapy. Measurements of CNV lesions were acquired by the confocal analysis of stained choroidal flat mounts. The proportions of T helper 17 (Th17) cells were determined by flow cytometric analysis. Results A total of differentially expressed 186 genes (120 up-regulated and 66 down-regulated) and 104 proteins (73 up-regulated and 31 down-regulated) were identified. The gene ontology and KEGG pathway analyses indicated that CNV was mainly associated with immune and inflammatory responses, such as cellular response to IFN-β and Th17 cell differentiation. Moreover, the key nodes of the protein–protein interaction network mainly involved up-regulated proteins, including alpha A crystallin and fibroblast growth factor 2, and were verified by Western blotting. To confirm the changes in gene expression, real-time quantitative PCR was performed. Furthermore, levels of IFN-β in both the retina and plasma, as measured by enzyme-linked immunosorbent assay (ELISA), were significantly lower in the CNV group than in the control group. IFN-β treatment significantly reduced CNV lesion size and promoted the proliferation of Th17 cells in laser-treated mice. Conclusions This study demonstrates that the occurrence of CNV might be associated with the dysfunction of immune and inflammatory processes and that IFN-β could serve as a potential therapeutic target.